201 great ideas for your small business - Applegate, Jane (Bloomberg series, 2011)
"Completely revised and updated edition of this very popular and successful small business book. The first edition of 201 Great Ideas for Your Small Business was hailed by management guru and author Tom Peters as "Brilliantly researched; Brilliantly written; A gem of priceless value on almost every page; Read; Inhale; Absorb; Great Stuff!." In this completely updated third edition of 201 Great Ideas for Your Small Business, renowned small-business expert and consultant Jane Applegate shares new, powerful, creative, simple, and proven approaches for building a better small business. Details how business owners can use online marketing and social networking more effectively. Offers timely strategies for thriving in challenging economic times. Includes scores of real-life success stories and all-new interviews with small-business owners, experts, and VIP's including Guy Kawasaki, Kay Koplovitz, and Michael Bloomberg. It may be small, but your business is a big deal to you, your customers, and employees. 201 Great Ideas provides lively, practical strategies to help you manage, grow, and promote your business"--